Distinctions Without a Difference? Preschool Curricula and Children's Development. Issue 3 (3rd July 2019) - Jenkins, Jade Marcus; Whitaker, Anamarie Auger; Nguyen, Tutrang; Yu, Winnie
Abstract: Public preschool programs require the use of a research-based, whole-child curriculum, yet limited research examines whether curricula influence classroom experiences and children's development. We use five samples of preschool children to examine differences in classroom processes and children's school readiness by classroom curricular status (curriculum/no curriculum), and across classrooms using different curricular packages. When a teacher reports using a curriculum, their classroom processes are indistinguishable from classrooms where teachers report using no curriculum. Some differences in classroom activities emerged across classrooms using different curricula; however, substantial variability exists across classrooms using the same curriculum. Head Start program fixed effects models and meta-analytic regressions reveal few associations between curricula and children's skills. Findings question whether preschool curricular policy benefit child development.